2001
DOI: 10.1128/mcb.21.14.4829-4836.2001
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria and Perinatal Lethality in Mice Lacking NEPH1, a Novel Protein with Homology to NEPHRIN

Abstract: A high-throughput, retrovirus-mediated mutagenesis method based on gene trapping in embryonic stem cells was used to identify a novel mouse gene. The human ortholog encodes a transmembrane protein containing five extracellular immunoglobulin-like domains that is structurally related to human NEPHRIN, a protein associated with congenital nephrotic syndrome. Northern analysis revealed wide expression in humans and mice, with highest expression in kidney. Based on similarity to NEPHRIN and abundant expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
310
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(319 citation statements)
references
References 18 publications
6
310
0
3
Order By: Relevance
“…Nephrin, a key player in the formation of the slit diaphragm, possesses extracellular IgGlike repeats, a single membrane-spanning region, and a cytoplasmic tail that interacts with intracellular molecules including CD2AP, which may anchor it to the actin cytoskeleton (17,18). The importance of this molecule in maintaining the glomerular barrier to protein is illustrated by the fact that humans with mutations in the NPHS1 gene and NPHS1-null mice are nephrotic and fail to develop normal podocyte foot processes (19,34). Many recent studies have associated reduced nephrin mRNA or protein expression with the onset of proteinuria in a number of nephropathies including diabetic nephropathy (35,36), minimal change disease (37), passive Heymann nephritis (38 -40), and membranous proliferative glomerulonephritis (37).…”
Section: Discussionmentioning
confidence: 99%
“…Nephrin, a key player in the formation of the slit diaphragm, possesses extracellular IgGlike repeats, a single membrane-spanning region, and a cytoplasmic tail that interacts with intracellular molecules including CD2AP, which may anchor it to the actin cytoskeleton (17,18). The importance of this molecule in maintaining the glomerular barrier to protein is illustrated by the fact that humans with mutations in the NPHS1 gene and NPHS1-null mice are nephrotic and fail to develop normal podocyte foot processes (19,34). Many recent studies have associated reduced nephrin mRNA or protein expression with the onset of proteinuria in a number of nephropathies including diabetic nephropathy (35,36), minimal change disease (37), passive Heymann nephritis (38 -40), and membranous proliferative glomerulonephritis (37).…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking NEPH1, a nephrin homolog sharing structural features as well as high renal expression with nephrin, develop severe nephrosis and die perinatally (75). Electron microscopy studies showed podocyte expression of NEPH1, and, in NEPH1-deficient mice, diffusely effaced foot processes.…”
Section: The Possible and The Actual: Animal Modelsmentioning
confidence: 99%
“…Defects in the podocin gene (NPHS2) manifest soon after birth and are characterised by uncontrolled, steroid-resistant proteinuria [3]. Mice lacking the gene encoding the nephrinlike protein NEPH1 (Kirrel) develop massive proteinuria and foot process effacement [4]. Mutations in the ACTN4 gene, which encodes alpha actinin 4, account for the familial form of focal segmental glomerulosclerosis with later onset of the disease [5].…”
Section: Introductionmentioning
confidence: 99%